2018
DOI: 10.1007/s11010-018-3326-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of factor XIII levels and polymorphisms on the risk of myocardial infarction in young patients

Abstract: Factor XIII (FXIII) stabilizes and protects the fibrin network. Its role in myocardial infarction (MI) is still to be clarified. To evaluate the association of FXIII levels with MI in young patients and to investigate how the FXIII-A p.Val34Leu, FXIII-B p.His95Arg, and IVS11, c.1952 + 144 C>G (Intron K) polymorphisms influence FXIII levels and MI risk. Patients with ST elevation MI below 40 years of age (MI, n = 119), age-matched clinical controls (CC, n = 101) without MI and coronary artery disease, and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
0
11
0
3
Order By: Relevance
“…This is the second study regarding FXIII activity in MI in young patients. A recently published study revealed significantly elevated FXIII activity in very young patients below 40 years of age, but the increase was limited to patients with STEMI [15]. Our study included patients with STEMI and NSTEMI.…”
Section: Discussionmentioning
confidence: 98%
“…This is the second study regarding FXIII activity in MI in young patients. A recently published study revealed significantly elevated FXIII activity in very young patients below 40 years of age, but the increase was limited to patients with STEMI [15]. Our study included patients with STEMI and NSTEMI.…”
Section: Discussionmentioning
confidence: 98%
“…Decreased FXIII levels were associated with the minor allele carriers at rs6003. (61,62) The negative association of the clot density with ALT was strongest in the participants who inherited the minor G allele. FXIII clearly plays a role in modulating clot structure by increasing the stability of the brin clot by altering its structure and increasing bre density.…”
Section: Discussionmentioning
confidence: 99%
“…In a short-term survival study, we recently demonstrated that after AMI, Factor XIIIA (FXIIIA) circulating levels are an independent predictor of major adverse cardiovascular events (MACE), in particular for heart failure (HF) and death [ 2 ]. On the contrary, the role of F13A1 gene variants in AMI onset, recurrence, and in post-AMI outcomes is still controversial, including gender disparities [ 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%